PENGGUNAAN METODE “RESEP MATEMATIKA” PADA MATERI OPERASI HITUNG BILANGAN PECAHAN - Indah Suciati (Koordinat Jurnal MIPA, 2022)
The fraction count operation is one of the problems often faced by students on the topic of fraction numbers. Even though the material is important and is often applied, there are still many students who make mistakes. The errors most often experienced by students are procedural errors. To solve this problem, a solution is given to the application of the "mathematical recipe" method. In this mathematical recipe method, students are given a clear and attractive format to organize important thoughts and information. As for the steps in using mathematical recipes, namely: (1) choosing the right mathematical procedure, (2) giving an example of how to use math recipe cards, (3) giving math recipe cards that are empty or half filled, and (4) ensuring participants students save math recipe cards for reference at a later date.